El papel de las actitudes subjetivas en la teoría de la responsabilidad penal de C. S. Nino: ¿un enfoque auténticamente objetivo? - Parmigiani, Matias (2022)
C. S. Nino's theory of criminal responsibility is known for being a liberal or anti-perfectionist theory. This means, first and foremost, that it stands against any attempt to link punishment with goals such as avoiding the selfdegradation of individuals or contributing to their own moral improvement. The state's coercive machinery is purported to fulfil an exclusive protective function, to the extent that not even blame is conceived any longer as part of the picture. Moreover, since blame usually involves assessing the features of an agent's guilty mind, such as her desires and beliefs, Nino's theory does also reject one of the most distinctive contributions of Criminal Law's dogmatic, on account of the perfectionist implications it would give rise to. As announced by its title, the objective of the present paper is to critically analyze the role that subjective attitudes play in Nino's theory. Although that role will be ultimately described as ambivalent and unclear, the main hypothesis defended here is that, in spite of Nino's assumptions, an adequate understanding of liberalism does not offer any reason to believe that subjective attitudes may not find after all a significant place within a liberal conception of criminal responsibility